CORRECTION OF VITAMIN-DEFICIENT CONDITIONS IN CHILDREN WITH ATOPY - E.A. Vishneva; R.M. Torshkhoeva; V.A. Barannik; Yu.G. Levina; K.E. Efendieva; A.A. Alekseeva (Педиатрическая фармакология, 2011)
The most important biochemical processes in human organism are carried out with vitamins and microelements involved. Acting as biological catalysts, vitamins have an impact on metabolism and provide protection against unfavourable environmental factors. The key source of vitamins and microelements for a person is food. The content of vitamins in a diet varies and depends on a range of various reasons. However, now the diet may not fully meet vitamin and microelement requirements. The result of this is widespread prevalence of sub-clinical deficiency of vitamins and microelements. Patients from one of the risk groups, children with atopy, are especially susceptible to this condition. Hypoallergenic diet prescribed as part of the therapeutic measures, is often the cause of imbalanced and irrational nutrition. Modern vitamin complexes may solve the issue of subnormal supply of vitamins and apparent hypovitaminosis in children with allergic diseases.Key words: polyvitamin complexes, atopy, allergic diseases, subnormal supply of vitamins, children.